Evolutionary strategies and adaptations for survival between mosquito-parasitic microsporidia and their intermediate copepod hosts: a comparative examination of Amblyospora connecticus and Hyalinocysta chapmani (Microsporidia: Amblyosporidae) - Andreadis, Theodore G. (Folia parasitologica, 2005)
The epizootiology, transmission dynamics, and survival strategies employed by two mosquito-parasitic microsporidia that utilize copepods as intermediate hosts are examined in relation to the biological attributes of their hosts and the environments in which they inhabit. Amblyospora connecticus Andreadis, 1988, a parasite of Ochlerotatus cantator (Coquillett) and Acanthocyclops vernalis (Fischer) is found in an unstable salt marsh environment that is subject to periodic flooding and drying. Both hosts have distinct non-overlapping generations. A. connecticus exhibits a well-defined seasonal transmission cycle that relies heavily on maternal-mediated transovarial transmission by female O. cantator during the summer, and horizontal transmission via the copepod host during the spring (copepod to mosquito) and fall (mosquito to copepod). Its survival strategies include: delayed virulence, low pathogenicity and high tissue specificity that allow for transstadial transmission of horizontally acquired infections and maximum spore production, reliance on living hosts throughout most of its life cycle with overwintering in the copepod, polymorphic development that is well synchronized with host physiology, and production and dissemination of infectious spores that are coincident with the seasonal occurrence of susceptible stages in each host. Hyalinocysta chapmani Hazard et Oldacre, 1975, a parasite of Culiseta melanura (Coquillett) and Orthocyclops modestus (Herrick) is found in a comparatively stable, subterranean habitat that is inundated with water throughout the year. Copepods are omnipresent and C. melanura has overlapping broods. H. chapmani is maintained in a continuous cycle of horizontal transmission between each host throughout the summer and fall but lacks a developmental sequence leading to transovarial transmission in the mosquito host. It relies on living hosts for most of its life cycle and overwinters in diapausing mosquito larvae. Transstadial transmission does not occur and there is no dimorphic development in the mosquito host. The spatial and temporal overlap of both mosquito and copepod hosts during the summer and fall affords abundant opportunity for continuous horizontal transmission and increases the likelihood that H. chapmani will find a target host, thus negating the need for a transovarial route. It is hypothesized that natural selection has favoured the production of meiospores in larval female mosquitoes rather than congenital transfer of infection to progeny via ovarian infection as a strategy for achieving greater transmission success. Analysis of the molecular phylogeny data suggest that (1) transovarial transmission and the developmental sequence leading to ovarian infection have been secondarily lost in H. chapmani, as they occur in all other closely related genera, (2) the ancestral state included complex life cycles involving transovarial transmission and an intermediate host, and (3) mosquito-parasitic microsporidia are adjusting their life cycles to accommodate host ecological conditions.